THE LEVEL OF GENERAL MOTOR PERFORMANCE OF YOUNG JUDOKAS IN SLOVAKIA (Fiep Bulletin - online, 2014)
Presently, we do not meet with serious health complications of people involved in sport, caused by hypokinesis, but we can observe relatively lower level of physical performance, in comparison with people involved in sports before the year 1990. The trend of lower physical performance, may however limit the performance of young judo competitors. Therefore in our studies, we tried to look into the general physical performance of young judo competitors, and compare it with data from before the year 1990. The aim of our work was to diagnose the level of conditioning skills using four variables, in 88 selected judo competitors - boys aged 14 to 16 years who were members of the center for talented youth in Slovakia. The results we had obtained were compared with the standards valid in the same age group until 1990. The Slovak Republic was at the time still part of Czechoslovakia. To elaborate collected data, we used basic statistical methods such as: arithmetic mean, standard deviation, minimum, maximum, variance, median and mode. We present the differences in motor performance in the transparent graphs. We came to the conclusion that in the medicine ball throw test subjects achieved better results in an average of 81 cm than in the past, in the test under-grip pull-ups on bar they were worse on average of 6 reps, in the depth of forward bend test in a standing position we also recorded worse performance by an average of 4.41 cm, in the rope climbing test they achieved better results on average by 0.52 seconds. In the two variables studied our group showed worse performances compared to the standards in the past. We see the cause especially in neglecting stretching exercises after the session, neglecting general physical training, as well as premature specialization in Judo. In contrast, in the two remaining variables our judokas achieved better performance compared to the standards in the past. They show higher levels of speed and explosive strength of upper extremities and back muscles. The main reason for better performance of our group is that the training focused on the specific muscles as well as the specificity of judo training.
Keywords: motor performance; youth; judokas